HARMONI DALAM KEBERAGAMAN: STUDI PLURALISME SOSIAL DI KOTA PEMATANG SIANTAR - Marpaung, Cindy Yohanna; Situmorang, Mey Roinda; Nababan, Yohana Inka Sari; Tampubolon, Silvia Nurhayati Br (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research aims to explore harmony in diversity in Pematangsiantar City, a city in North Sumatra which is known for its ethnic, cultural and religious diversity. Using a qualitative approach, this study investigates the factors that contribute to the creation of social pluralism and harmonious intergroup relations in the city. Data was collected through in-depth interviews with key stakeholders, participant observation, and documentation studies. Research findings reveal that religious tolerance, respect for cultural differences, and cooperation between communities are values that are deeply embedded in Pematangsiantar society. In addition, the role of formal and informal leaders, as well as local initiatives in facilitating dialogue and interaction between groups also contribute significantly to social harmony in this city. This research contributes to a deeper understanding of social pluralism and how it can be achieved in diverse societal contexts.